Catastrophic inflammatory death of monocytes and macrophages by overtaking of a critical dose of endocytosed synthetic amorphous silica nanoparticles/serum protein complexes. (July 2013) - Fedeli, Chiara; Selvestrel, Francesco; Tavano, Regina; Segat, Daniela; Mancin, Fabrizio; Papini, Emanuele
Aims: We tested whether phagocytic monocytes/macrophages are more susceptible than nonphagocytes to nanoparticle (NP) toxicity.Materials & methods: We compared in vitro cell death and proinflammatory cytokine production in human monocytes, macrophages, lymphocytes and HeLa cells due to synthetic amorphous silica (SiO2 )-NPs in different serum concentrations and correlated them with cellular uptake and distribution.Results: Phagocytes were approximately ten-times more sensitive than nonphagocytes to SiO2 -NPs and more effectively endocytosed SiO2 -NP–serum protein nanoagglomerates, so determining their accumulation in acidic endocytic compartments well beyond a critical/cytotoxic threshold. Monocyte/macrophage death was paralleled by cytokine secretion.Conclusion: The physiological specialization of monocytes/macrophages to effectively capture NPs may expose them to the risk of catastrophic inflammatory death upon saturation of their maximal storage capacity. Original submitted 9 March 2012; Revised submitted 3 August 2012; Published online 13 December 2012